Reflexive competence of adult education professionals in political adult education - Ekkhard Nuissl; Simona Sava (Firenze University Press, 2018)
The article examines the reflexive competence for professionals in adult education, mainly political adult education. Reflexive competences can solve teaching tasks in settings, in which adult learners are confronting with challenging current topics, such as populism and Euroscepticism. In spite of their differences, these two political phenomena demand innovative pedagogical approaches. A meta-level analysis of the reflexive competence highlights, on the one hand, the ways in which it can be fostered in adult learners, so that they may be capable to handle political questions in a holistic perspective, and, at the same time, how adult educators can master it both as a pedagogical strategy and a self-reflection process. Both analytic and descriptive considerations are provided, drawing on the different aspects defining the reflexive competence in the light of political education, so as to contribute to the professional development of adult educators and to improve practice in didactical settings.   La competenza riflessiva dei professionisti dell'educazione degli adulti nelle politiche di educazione degli adulti L'articolo si propone di analizzare la competenza riflessiva, necessaria per tutti i professionisti che lavorano nell'ambito dell'educazione degli adulti e con responsabilità politiche. Le competenze riflessive aiutano nel far fronte a sfide, complesse ed attuali, come il populismo e l'euroscetticismo. Seppure essi siano fenomeni distinti, entrambi richiedono la definizione di approcci pedagogici innovativi. Una analisi meta-livello della competenza riflessiva è utile per evidenziare i modi in cui essa può essere promossa tra adulti in apprendimento capaci di acquisire da un lato strumenti utili per la gestione di processi decisionali con approccio olistico e dall'altro per definire strategie educative e processi di riflessività. Il contributo offre elementi descrittivi e di analisi a partire dalle varie componenti della competenza riflessiva nelle politiche educative in quanto rilevanti per lo sviluppo professionale dei professionisti dei processi formativi e per il miglioramento di pratiche e azioni educative.